2021
DOI: 10.1097/mao.0000000000003141
|View full text |Cite
|
Sign up to set email alerts
|

Transcanal Endoscopic Cartilage and Perichondrium Graft Myringoplasty for Large Tympanic Membrane Perforations

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous study suggested that the perichondrium overlaying the epithelial layer of double layer graft and everted edges of traumatic perforation didn't induce the iatrogenic cholesteatoma. [21][22][23] On the contrary, the pearl formations were found in 5.3% patients even if the perforation margins and the squamous epithelium of TM remnant were removed completely in interlay myringoplasty with anterior subannular grafting technique for anterior and subtotal perforations. 13 In this study, 72.3% patients completed 3 years followup and performed temporal bone CT examination, CT revealed the well pneumatization of mastoids and middle ear.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study suggested that the perichondrium overlaying the epithelial layer of double layer graft and everted edges of traumatic perforation didn't induce the iatrogenic cholesteatoma. [21][22][23] On the contrary, the pearl formations were found in 5.3% patients even if the perforation margins and the squamous epithelium of TM remnant were removed completely in interlay myringoplasty with anterior subannular grafting technique for anterior and subtotal perforations. 13 In this study, 72.3% patients completed 3 years followup and performed temporal bone CT examination, CT revealed the well pneumatization of mastoids and middle ear.…”
Section: Discussionmentioning
confidence: 98%
“…However, Ahmed et al 17 performed chondroperichondrial clip myringoplasty by directly spreading the overlying perichondrium over the superficial surface of the tympanic membrane and did not observe any middle-ear cholesteatoma during a follow-up period of 12-26 months. Lou and colleagues 18,19 applied the cartilage and perichondrium double-layer graft technique without removing the superficial epithelium to repair large perforations, and found no middle-ear cholesteatoma over a follow-up period of 28.2 ± 6.1 months. However, other groups reported middle-ear cholesteatoma following application of the underlay technique.…”
Section: Discussionmentioning
confidence: 99%
“…The recent bibliography specifies the interest of the new endoscopic approach, particularly in the repair of large perforations; transcanal endoscopic myringoplasty for large tympanic membrane perforations using a double-layer perichondrium and cartilage graft is feasible with comparable rates of closure to more invasive approaches [ 24 ]. And new other therapeutic methods have been published with the aim to improve therapeutic results in the repair of eardrum perforations such as the use of cartilage-perichondrium double graft combined with basic fibroblast growth factor, which has been demonstrated as effective method for providing the long-term graft success rate of the perforations with extensive epithelialization [ 25 ].…”
Section: Discussionmentioning
confidence: 99%